Regulation of Foreigner Stay Permit as Director of Limited Liability Company and Investor in Foreign Investment - Tri Sutjiati; Ida Ayu Sadnyini (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
Based to Article 10 Paragraph (1) on Regulation Ministry of Manpower Number 10 Year 2018 Concerning Procedure of Employ Foreign Worker says that employer of the foreign worker is not required to possess any EPP (working permit) to employ foreign workers who are shareholders with the position of the board of directors or board of commissioners, as it is stated before on Article 10 Paragraph (1) Presidential Decree No. 20 Year 2018 Concerning Foreign Worker. Nevertheless, the facility for investors to possess stay permits in Indonesia which is mentioned in Article 22 Paragraph (3), Regulation of Ministry of Justice and Human Rights Number 51 Year 2016 Concerning Change of Regulation Number 24 Year 2016 Concerning Technical Procedures for Application and Issuance of Visit Visas and Limited Stay Visas, says that the investor prohibited working. This study aims to investigate the procedure and the regulations that govern temporary stay permits of directors and foreign investors in Indonesia. The method used in this study is normative legal research and meanwhile, statute approach and conceptual approach are used as the approach of this study. The results of this study showed that 1) higher norms govern action, as to create lower norms, governs realization of action. Presidential Decree has a higher position in the hierarchy from Ministry Regulations. 2) ideal framework of statutory regulations shall consist of a balance portion of justice, legal certainty and finality.